Beneficial organisms in biological control strategies - entomopathogenic fungi - Augustyniuk-Kram, Anna (Studia Ecologiae et Bioethicae, 2010)
Fungal entomopathogens are widespread in nature and contribute to the natural regulation of insects. They can be exploited for pest management as biological control agents of pests in attempts to improve the sustainability of crop protection. Four types of biological control are recognized: classical, inoculation, inundation, and conservation biological control. Classical biological control is the intentional introduction and permanent establishment of an exotic biological agent for long-term pest management. Inoculation biological control is the intentional release of a living organism as a biological control agent with the expectation that it will multiply and control the pest for an extended period, but not permanently. Inundation biological control is the release of large numbers of mass-produced biological control agents to reduce a pest population without necessarily achieving continuing impact or establishment. Conservation biological control is a modification of the environment or existing practices to protect and enhance specific natural enemies or other organisms to reduce the effect of pests. The traditional and the most popular approach in biological control with entomopathogenic fungi has been to apply the fungal material to the cropping system (as biopesticide), using an inundation biological control strategy. The term biopesticide is used for microbial biological pest control agents that are applied in a similar manner to chemical pesticides. The use of biopesticides can substitute for some (but not all) chemicals and provide environmentally safe and sustainable control of pests but EU legislation and prohibitive registration costs are discouraging the development and commercialization of many promising new products.